SPECTRA OF VIBRATION SIGNALS WHICH ALLOW TO REVEAL DEFECTS IN GEAR TRACTION DRIVE ELECTRIC TRAINS - , Д. Ю. (Municipal economy of cities. Series: «Economy science», 2013)
Different types of defects in the gear trains. Vibro offers modern technology that can detect and prevent failures, to maintain operational performance within specified limits and to predict the level of technical parts and components to continue their service life.